2018
DOI: 10.3389/fnins.2018.00486
|View full text |Cite
|
Sign up to set email alerts
|

Selanylimidazopyridine Prevents Lipopolysaccharide-Induced Depressive-Like Behavior in Mice by Targeting Neurotrophins and Inflammatory/Oxidative Mediators

Abstract: Inasmuch, as the major depressive disorder (MDD) has been characterized as a heterogeneous disease as the inflammatory processes, neurotrophic factors’ dysfunction and oxidative/nitrosative stress are believed to play a vital role in its establishment. Organoselenium compounds stand out due to their antioxidant, anti-inflammatory, neuroprotective, and antidepressant effects. In this sense, the present study investigated the effect of 3-((4-methoxyphenyl)selanyl)-2-phenylimidazo[1,2-a]pyridine (MPI; 20 and 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In the search for new potential antidepressant-like compounds, the same group synthesized and demonstrated the antidepressant activity of another N -heterocycle derivative, 3-(( p -methoxyphenyl)selanyl)-2-phenylimidazo[1,2-a]pyridine (Domingues et al 2018 , 2019 ). Very recently, an isoquinoline derivative has been reported as an antidepressant-like compound that selectively and reversibly inhibited cerebral monoamino oxidase (MAO) B activity in C57Bl/6 mice (Sampaio et al 2016 , 2020 ).…”
Section: Pharmacology Of Organoselenium Compoundsmentioning
confidence: 99%
“…In the search for new potential antidepressant-like compounds, the same group synthesized and demonstrated the antidepressant activity of another N -heterocycle derivative, 3-(( p -methoxyphenyl)selanyl)-2-phenylimidazo[1,2-a]pyridine (Domingues et al 2018 , 2019 ). Very recently, an isoquinoline derivative has been reported as an antidepressant-like compound that selectively and reversibly inhibited cerebral monoamino oxidase (MAO) B activity in C57Bl/6 mice (Sampaio et al 2016 , 2020 ).…”
Section: Pharmacology Of Organoselenium Compoundsmentioning
confidence: 99%
“…BDNF is a major representative of the brain neurotrophic factors, which are involved in cognition control. Cognitive dysfunction in depressive patients is due to decreased levels of BDNF (Domingues et al, 2018), and BDNF has been suggested to influence the response to antidepressant treatment (Hennings et al, 2019). Therefore, the effect of rhFGF21 on BDNF expression was measured.…”
Section: Exogenous Rhfgf21 Could Function Through Fgfr1 Activationmentioning
confidence: 99%
“…Several hypotheses to explain the pathology of depression, including glutamatergic excitotoxicity, monoamine system impairment, hypothalamic-pituitary-adrenal axis dysfunction, neuroinflammation, and neural plasticity and neurogenesis disruption, have emerged (Taniguti et al, 2019). Among these hypotheses, inflammatory processes have been suggested to be involved in the etiology of depression in many studies (Domingues et al, 2018). Increasing amounts of preclinical and clinical research have shown that proinflammatory cytokines might contribute to depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple administrations of LPS increase the expression of inflammatory related markers and lead the immune activation and ROS production in brain. These events are reported to accumulate beta amyloids (Aβs) in the cerebral cortex and hippocampus [29]. We found that, LPS-induced mice expressed high levels of malondialdehyde (MDA) that indicated the enhancement of lipid peroxidation and produced oxidative stress in the brain.…”
Section: Discussionmentioning
confidence: 94%